2010
DOI: 10.1016/j.urology.2010.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated RhoA/Rho-kinase Signaling in Penis of Transgenic Sickle Cell Mice

Abstract: Objectives RhoA and its main downstream effector, Rho-kinase (ROCK) are important in maintaining the penis in the flaccid state. The pathophysiology of Sickle cell disease-associated priapism is not well defined. We hypothesize that RhoA/ROCK vasoconstrictive pathways may be involved in the development of priapism. Therefore, the objective of this study was to evaluate molecular changes in RhoA and ROCK in an established transgenic sickle cell mouse model of priapism. Methods Two groups of mice were utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 25 publications
3
40
0
1
Order By: Relevance
“…It has been well established that the Rho pathway, consisting of RhoA and its downstream effector, ROCK (with two isoforms, ROCK1 and ROCK2), plays a major role in maintaining the penis in its flaccid state through vasoconstriction and eNOS regulation 25, 26 . In fact, recently, Bivalacqua et al demonstrated that the RhoA/ROCK pathway is downregulated in the penis of SCD mice and thus contributes to uncontrolled cavernosal vasorelaxation producing priapism 11 . Specifically, they showed that the SCD mouse penis has a significant decline in both RhoA and total ROCK activities compared with that of the WT mouse penis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been well established that the Rho pathway, consisting of RhoA and its downstream effector, ROCK (with two isoforms, ROCK1 and ROCK2), plays a major role in maintaining the penis in its flaccid state through vasoconstriction and eNOS regulation 25, 26 . In fact, recently, Bivalacqua et al demonstrated that the RhoA/ROCK pathway is downregulated in the penis of SCD mice and thus contributes to uncontrolled cavernosal vasorelaxation producing priapism 11 . Specifically, they showed that the SCD mouse penis has a significant decline in both RhoA and total ROCK activities compared with that of the WT mouse penis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, upon psychogenic or reflexogenic neuronal stimulation, prolonged erection occurs because of uncontrolled nNOS-dependent cGMP-induced vasodilation of the corpora cavernosa owing to deficient PDE5-specific cGMP hydrolysis 9 . More recently, priapism in SCD mice has also been shown to be associated with dysfunctional signaling of RhoA, and its downstream effector ROCK, which both mediate vasoconstriction of the penile vasculature 11 . In addition, dysregulation of opiorphin and adenosine signaling, as well as increased oxidative stress in the penis, are proposed contributory mechanisms based on experimental studies using animal models of priapism 1116 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bivalacqua et al reported that total ROCK activity in eNOS knock-out mice, which demonstrate a priapism phenotype, was reduced, with no change in RhoA activity [20]. Bivalacqua et al later reported attenuated RhoA/ROCK signaling in penes of transgenic SCD mice contributing to priapism [35]. Penes of SCD mice display a reduction in RhoA activity and specifically ROCK2 protein expression compared to that of the wild-type mouse penis.…”
Section: Molecular Mechanisms Of Priapism Pathophysiology (Figure 1)mentioning
confidence: 99%
“…Recognition of the roles of NO, RhoA/ROCK, adenosine, and opiorphins may lead to the development of future agents potentially targeting these molecular effectors. 39,[46][47][48]105,106 Strategies involving the use of PDE5 inhibitors to correct the underlying aberrations in NO balance have met with some success, as well as challenges regarding cost and patient adherence. [51][52][53]107 Preclinical investigations in animal models of SCD have uncovered alternative methods of restoring NO balance through the use of sustained NO-releasing compounds.…”
Section: Future Perspectivesmentioning
confidence: 99%